Information seeking behaviour of generation Y students at the Stellenbosch University Library and information service - Adams, Lindall Elaine (University of the Western Cape, 2014)
Magister Bibliothecologiae - MBibl === The project examines the information seeking behaviour of a small group of so-called Generation Y students at the Stellenbosch University as they undertake an academic assignment. There is consensus across the world that universities need to adapt to the needs of Generation Y students, brought up with high-level information technology, the internet and social networking. However, research shows that this does not mean that they are information literate. They have high-tech skills but often do not know how to analyse an information need or discriminate between information sources. Information scientist Carol Kuhlthau develop the ISP model upon which the study was based. Her model sees information seeking as a complex cognitive and affective process. Successful seekers have learned how to manage the process. University libraries need to adapt their information retrieval systems and services to meet the needs of their new kinds of students. The study, a small-scale intensive qualitative case study, hopes to provide insight into how they might do this. The researcher collected data while the participants were writing the assignment. Data gathering methods included interviews, journal writings and questionnaires. === South Africa